Obsidian balls (marekanite) from Cerro Tijerina, central Nicaragua: petrographic investigations - Mrazova,S.; Gadas,P. (Journal of Geosciences, 2011)
The paper describes a find of volcanic glass in central Nicaragua. We investigated obsidian samples in perlite from a large profile of volcanic rocks (Cerro Tijerina) in the vicinity of the town of Matagalpa. The obsidian occurs in the form of up to 3-cm dark-coloured balls (spheres) randomly distributed in brittle grey perlite, which also has spherulitic texture. These balls, previously called marekanite, are characterised by an abundance of microphenocrysts (feldspar, biotite, amphibole, apatite and magnetite). Microprobe analysis of the homogenous glass of obsidian balls and perlite has confirmed their subalkaline, and particularly high-K calc-alkaline character (SiO2 ≥ 70 %, Na2O+K2O < Al2O3), which is typical for rhyolitic melts. A sharp contact was observed between the core and the surface layer (approx. 0.1-0.2 mm) of the obsidian balls, reflecting changes in the H2O content.
Keywords: obsidian; marekanite; volcanic glass; Cerro Tijerina; Nicaragua